Jews in ancient and medieval Armenia: first century BCE to fourteenth century CE - Stone, Michael E. (Oxford University Press, 2022)
"It has long been the general opinion that there was no significant Jewish community in Armenia throughout the centuries. This book examines the evidence from written sources to archaeological discoveries and asserts that there were Jews in Armenia in the ancient and mediaeval periods. Tigran the Great transferred Jewish exiles to Armenia in the first century BCE. They settled in the chief cities of the land and were still there in the fourth century CE. There were Jews in the capital city Dvin in the late ninth century and Jewish tombstone inscriptions from Southern Armenia witness a community there during the Seljuk and Mongol conquests. Thus, the conventional picture must be changed"--